Oxidative ethanol dry reforming for production of syngas over Co-based catalyst : Effect of reaction temperature - Fahim, Fayaz; He, Chao; Goel, Avishek; Rintala, Jukka; Konttinen, Jukka (Elsevier Ltd, 2023)
Till date, oxidative ethanol steam reforming use Ni-based catalysts to produce syngas. However, Ni catalysts suffer from easy deactivation due to the coke formation at low temperatures. Therefore, oxidative ethanol dry reforming is a promising method and was investigated over 10 %Co/Al2O3 catalyst due to their high activity and stability to produce high-quality syngas. More importantly, the syngas can be upgraded to produce liquid biofuels and chemicals. The catalyst was evaluated in a quartz fixed-bed reactor under atmospheric pressure at PCO =PO= 5 kPa, PC = 15 kPa, with reaction temperature ranging between 773 and 973 K. The γ-Al2O3 support and 10 %Co/Al2O3 catalyst had BET surface areas of 175.2 m2 g−1 and 143.1 m2 g−1, respectively. Co3O4 and spinel CoAl2O4 phases were detected through X-ray diffraction measurements on the 10 %Co/Al2O3 catalyst surface. H2-TPR measurements indicate that the 10 %Co/Al2O3 catalyst was completely reduced at a temperature beyond 1000 K. NH3-TPD measurements indicated the presence of the weak, medium, and strong acid sites on the γ-Al2O3 support and 10 %Co/Al2O3 catalyst. Due to increased reaction temperature from 773 to 973 K, C2H5OH and CO2 conversions improved from 22.5 % to 93.6 % and 16.9–52.8 %, respectively. Additionally, the optimal yield of H2 and CO obtained at 68.1 % and 58.3 %, respectively. Temperature-programmed oxidation experiments indicated that the amount of carbon deposition was the lowest (28,92 %) at 973 K and increased by 41.48 % at 773 K.